Optimizing The Role Of Da'wah Bil Hal For The Young Generation In The Modern Era - Nasrillah MG; Fathir Rizky; Ahmad Arief; Paris Hibatullah; Syaiful Izhar Dalimunte (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Da'wah is an obligation of Muslims, especially those who already have knowledge of the Islamic religion, according to the limits of their respective abilities. Da'wah is an effort to convey the teachings of the Islamic religion by a person/group of people to a person or group of people so that they believe/understand and practice Islamic teachings correctly. So in da'wah the goal is to change the beliefs, knowledge and behavior of the target of the da'wah in accordance with Islamic teachings. The aim of this article is to find out about optimizing the role of da'wah bil hal in the younger generation in the modern era. The conclusions in this article are: 1. Da'wah is the obligation of Muslims, especially those who already have knowledge of the Islamic religion, according to the limits of their respective abilities. 2. Da'wah bil-hal is an effort to da'wah by carrying out concrete actions, of course it takes various forms, it can be in the form of assistance given to other people, both moral and material assistance. 3. Because technological advances have created a habit that has formed the current millennial generation which is very dependent on technology, which makes today's millennials spend more of their time interacting using social media, such as; Instagram, WhatsApp, Telegram and so on. This is actually an opportunity that should be used well, by taking advantage of these habits, such as creating religious content that is packaged as attractively as possible, and in accordance with current conditions and things that today's millennials will be interested in knowing. The content in preaching is not just monotonous lectures, but the content must include virtual elements, such as quotes, memes, comics, scripts, video vlogs and so on.